Komparasi Zuhud Al-Ghazali dan Asketisme Protestan Max Weber: (Kajian Nilai Spiritualitas di Antara Orientasi Duniawi dan Transendental) - iwan shohib el hasan (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2026)
This article aims to describe the concepts of asceticism by Max Weber and zuhud in Islam from the perspective of Al-Ghazali. At a glance, both concepts emphasize regulating individuals to avoid excessive greed in pursuing worldly wealth. However, asceticism originates from Protestantism, whereas zuhud is an integral part of Sufism in Islam. This article employs a qualitative descriptive research method with a comparative technique. The approach utilized in this study frames economics as the implication of both concepts. The findings indicate a definitive theological similarity. Max Weber's asceticism and Imam Al-Ghazali's perspective on zuhud both encourage individuals to restrain themselves from materialism and to utilize worldly materials as a means to achieve spiritual values. However, differences emerge when analyzed through a socio-economic lens. Max Weber's asceticism is more oriented towards work ethic, efficiency, and capitalism as manifestations of religious faith, whereas Al-Ghazali emphasizes transcendent values focusing on balance and the moral sustainability of society. This study is expected to enrich the literature on the relationship between religion, economics, and society, providing a foundation for further integrative studies in these domains.